Prawda w świetle znowelizowanego kodeksu postępowania cywilnego - Brzemia-Bonarek , Aleksandra (Prawo Kanoniczne, 2008)
The article is a short review of the changes in Polish civil law procedure connected with the minimization of the „objective truth” principle. The aim of the novelization was to accelerate the judges in their work, fulfil UE standards and regulations, and to activate the parties to responsible and diligence participation in the civil litigation. The author generally agrees with the necessity of changes the procedural rules which have been set out by Polish Parliament, although in her critical point of view, judge’s duty to adjudicate according with the objective truth – should never be inhibit.